Orthodontic Camouflage Treatment of a High-Angle Severe Skeletal Class II Discrepancy - Marshadhianti, Deryana; Purwanegara, Miesje Karmiati (Journal of Dentistry Indonesia, 2019)
Proper orthodontic treatment in adult patients with severe skeletal Class II discrepancy can be challenging. Recently, miniscrew implants have been used as a strategy to treat skeletal Class II patients. Objective: This report illustrates a skeletal Class II malocclusion management combining straight wire technique and miniscrew implant anchorage. Case report: The patient was a 21-years- old Indonesian female with Class II skeletal discrepancy, a retrognathic mandible, a high mandibular plane angle, and a mouth breathing habit due to a history of allergic rhinitis. Anchorage control is important in the sagittal and vertical directions. Miniscrew implants were placed in the interradicular ar ea bet ween t he upper second pr emolar and fir st mol ar on bot h sides. Further more, en -masse retraction of the six anterior teeth was performed using miniscrew implants as the anchorage. After 16 months of treatment, esthetics and function were improved and the chief complaint of the patient was resolved. Class I canine and incisor relationship was achieved. These mechanics contributed to the correction of the gummy smile of this patient. Conclusion: Placement of miniscrew implants in the posterior regions of the maxilla effectively camouflaged a high-angle skeletal Class II discrepancy. This technique requires minimal patient compliance and is useful for the correction of high-angle cases in adult patients.